2008
DOI: 10.1152/japplphysiol.01380.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of overground vs. treadmill walking in healthy individuals

Abstract: The goal of this study was to compare treadmill walking with overground walking in healthy subjects with no known gait disorders. Nineteen subjects were tested, where each subject walked on a split-belt instrumented treadmill as well as over a smooth, flat surface. Comparisons between walking conditions were made for temporal gait parameters such as step length and cadence, leg kinematics, joint moments and powers, and muscle activity. Overall, very few differences were found in temporal gait parameters or leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
332
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(355 citation statements)
references
References 28 publications
18
332
2
3
Order By: Relevance
“…This is contrary to previous studies, where up to 130% larger RF EMG values were reported during the MT condition while walking [3,4,5]. These differences are possibly due to walkway limitations (< 8 m), an elliptical walkway or inconsistent footwear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is contrary to previous studies, where up to 130% larger RF EMG values were reported during the MT condition while walking [3,4,5]. These differences are possibly due to walkway limitations (< 8 m), an elliptical walkway or inconsistent footwear.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have compared motorised treadmill vs overground locomotion to examine kinematics [1], ground reaction forces [2] and muscular activation differences [3,4,5]. Similarly, non-motorised treadmill and overground locomotion have been compared for 5000 m performance time, electromyography (EMG), blood lactate, oxygen uptake kinetics, heart rate [6], maximal sprinting performance [7] and 6-minute walk distance [8] that have all highlighted dissimilarities between the conditions which could affect the mechanical loading environment and also the musculoskeletal adaptations generated by different locomotion conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, over ground gait velocity increased post adaptation due to increased stride length and decreased stride duration after Motor adaptation during treadmill walking [20]. Lee and Hidler results also suggested that when neurologically impaired individuals walk on a treadmill, they modify their muscle activation patterns and subsequently joint moments and powers [21].…”
Section: Discussionmentioning
confidence: 97%
“…Such differences include shorter step lengths, higher cadence and a shorter swing phase on treadmill compared to over-ground walking and subjects not receiving the same visual stimulation possibly altering balance strategies [26,39]. Although these differences may affect walking outcomes for LBP, this requires further research.…”
Section: Discussionmentioning
confidence: 99%